Competition, Land Prices, and City Size - Sergey Kichko (Center for Economic Studies and ifo Institute (CESifo), 2019)
Larger cities typically give rise to two opposite effects: tougher competition among firms and higher production costs. Using an urban model with substitutability of production factors and pro-competitive effects, I study the response of the market outcome to city size, land-use regulations, and commuting costs. For industries with low input shares of land, larger cities host more firms setting lower prices whereas for sectors with intermediate land shares larger cities accommodate more firms charging higher prices. Softer land-use regulations and/or lower commuting costs reinforce pro-competitive effects, making larger cities more attractive for residents via lower prices and broader product diversity.
Keywords: L11; L13; R13; R32; R52; 330; land prices; pro-competitive effects; city size; product diversity; land-use regulations